A Critical Study of Translation of Proper Names in Fantasy Literature - Hamed Shanaki; Samar Ehteshami (فصلنامه نقد ادبی, 2022)
Literary proper names can perform various functions. In fantasy literature, which usually has its own dedicated secondary world, these functions are even more prevalent. Analyzing the translation of these names provides new insights for translators of the genre and literary translators in general. In that light, the present study was designed to analyze the translation of proper names in five fantasy novels. To conduct the research, first the proper names in fantasy novels were identified and their functions were determined based on Gibka’s model (2018). Then by analyzing the translation of the proper names from English to Persian, the translation strategies were identified and examined. After the analysis of data, it became evident that contrary to popular belief, non-translation is not always the best strategy for translating literary names. Based on the results, the strategy of translation never caused the loss of semantic function in the translated texts, while in some cases the non-translation strategy caused the loss. Moreover, non-translation never caused the loss of localization function. Therefore, choosing the translation strategy for proper names with secondary functions in mind will help translators transfer these functions to the target text more effectively. Extended abstract Introduction Translation of proper names in fantasy literature can be a contentious topic among translators and theorists alike, since literary proper names can perform different functions within the narrative. The present research was conducted in order to determine the different functions of proper names in fantasy literature and the strategies employed for translating those names and to see if and how the translation strategy affects the proper name function in the target text. Methodology The present study was an empirical, descriptive and analytical research, conducted in order to analyze proper names and their translation in the fantasy genre. The corpus of this study was a parallel, bilingual one. It consisted of the novels, “Prince of Fools”, “The Liar's Key”, “Shadow and Bone”, “Everless”, and “Bone Season” and their Persian translations. These novels were translated to Persian within the last ten years (2014 – 2017) and could indicate recent trends in the translation of proper names in the fantasy genre in Iran. The novels were wholly read with a purposive sampling method, and all of the proper names were extracted. Proper names were then classified using the eight relations and the twenty-two permanent secondary functions defined by Gibka (2018) which were applied to both the source text’s proper names and their translations in the target text. The data was analyzed at the lexical level. Each name along with the titles or other modifiers, were considered as one unit. Then, Van Coillie’s (2006) ten strategies for translating proper names were used as to analyze the translation of proper names. Results and Discussion In total 426 proper names were found and analyzed, out of which 214 had secondary functions. Among the proper names with secondary functions, the semantic function was the highest, followed by the localizing and sociological functions. Some of the proper names had two or three overlapping functions. Semantic and localizing were the two functions that overlapped the most (13 proper names), followed by localizing and sociological (11 proper names). After the analysis, it became evident that most proper names’ functions stayed the same in the translation. All in all, no proper name changed its function in the process of translation and among proper names with no secondary functions, none gained new ones. However, there were cases in which the secondary function was lost or delayed in the process of translation. Loss of function happened only for 11 semantic proper names and one localizing proper name, while no allusive and sociological proper name lost its function. The only translation strategy that caused the loss of function in semantic proper names was non-translation. Regarding the localizing proper name, phonetic adaptation was the strategy that caused the loss of function. Furthermore, delay of function happened for proper names with the semantic function and one proper name with the humorous function, and it only occurred when the proper name was transferred using the “non-translation plus additional explanation” strategy, where the additional strategy was in the form of a footnote or an endnote. Conclusion One of the important findings of this study was that while examining the translation strategies, some translation strategies were detected which had not been included in Van Coillie’s model (2006), namely combinations of different strategies, and in two cases, additional explanations added to a strategy other than non-translation (i.e. “replacement by a counterpart in the target language”, and “translation”). Furthermore, it did not relate the strategies to the secondary functions of literary proper names. However, the delay of function was the only issue that was not included in Gibka’s model (2018), which might be because this delay is probably specific to proper names in translated texts. Keeping this in mind, Gibka’s (2018) model can be effective for analyzing the translation of proper names in fantasy literature. The results of this research can be useful for translation research and theory. This study showed that the “translation” strategy never caused the loss of the “semantic” function, while the “non-translation” strategy did cause this loss. So the “translation” strategy can potentially be an effective strategy for semantic proper names, while translator should be careful when using the “non-translation” strategy with semantic proper names, as the loss of function is likely to occur. This can help translators who are working in the fantasy genre to gain a deeper understanding of the relationship between the secondary functions of proper names and the translation strategies. The results of this research can also benefit translation students in classes such as “literary translation”, since it indicates the significance of proper names and the attention that their translation requires, specifically in the fantasy genre.